Safe drinking water: Critical components of effective inter-agency relationships - Jalba, D.; Cromar, N.; Pollard, S.; Charrois, Jeffrey; Bradshaw, R.; Hrudey, S. (Pergamon, 2010)
The paper supports the development of evidence-based emergency management frameworks of cooperation between agencies in the area of drinking water and public health, as part of developing the overall risk management culture within water utilities. We employed a qualitative research design to understand critical gaps in inter-agency relations that aggravated past drinking water and health incidents and from these identified determinants of effective relationships. We identified six critical institutional relationship components that were deficient in past incidents, namely proactivity, communication, training, sharing expertise, trust and regulation. We then analysed how these components are addressed by reputable water utilities and public health departments to develop positive examples of inter-agency cooperation. Control of different risks (e.g. public health, business, and reputation) resulting from drinking water incidents should employ a preventive framework similar to the multiple barrier approach for management of drinking water quality.